2014
DOI: 10.21608/jesaun.2014.115063
|View full text |Cite
|
Sign up to set email alerts
|

Grain Refinement of Commercial Pure Aluminium by Zirconium

Abstract: The effect of Zr addition on the grain refinement of commercial pure aluminium (99.7%) has been investigated in the present study. The results showed that addition of up to 0.3wt. % Zr significantly decreases the average grain size of aluminium from 1100 µm to 162 µm at holding time of 90 seconds. The refining effect of zirconium is attributed to the presence of Al 3 Zr particles in Al-Zr master alloy. These particles are acting as effective heterogeneous nucleating sites for α-Al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Mahmoud et al [29] added 0.1 to 0.3 wt.% Zr (with 0.05 wt.% Zr step) to pure Al and found that the grain structure has been refined in the experimental range. However, further Zr addition (>0.3 wt.%) slightly increased the average grain size, whereas excess Zr addition did not show any considerable effect on the Al structure [29]. It was reported by Rohrer [30] that precipitation of a second phase is one mechanism that can occur to partition excess solute in the microstructure.…”
Section: Microstructure and Grain Size Analysesmentioning
confidence: 99%
“…Mahmoud et al [29] added 0.1 to 0.3 wt.% Zr (with 0.05 wt.% Zr step) to pure Al and found that the grain structure has been refined in the experimental range. However, further Zr addition (>0.3 wt.%) slightly increased the average grain size, whereas excess Zr addition did not show any considerable effect on the Al structure [29]. It was reported by Rohrer [30] that precipitation of a second phase is one mechanism that can occur to partition excess solute in the microstructure.…”
Section: Microstructure and Grain Size Analysesmentioning
confidence: 99%